3458 Temporal Trends and Outcomes of Opioid Abuse among Adolescents & Young Adult Sickle Cell Disease Patients. (27th March 2019) - Onyeakusi, Nnaemeka E; Oshunbade, Adebamike; Mukhtar, Fahad; Adejumo, Adeyinka; Gbadamosi, Semiu; Onwudiwe, Chinonso
Abstract : OBJECTIVES/SPECIFIC AIMS: In this study, we aim to describe temporal trends in opioid abuse among adolescents and 11-21years and young adults 22-35years with Sickle cell disease hospitalized for sickle cell crisis. We also aim to evaluate clinical and healthcare utilization outcomes of opioid abuse in the same population. In addition, we hope to assess for difference in effect by age category. METHODS/STUDY POPULATION: Our study is a cross-sectional study of data secondarily sourced from the 2007-2014 National Inpatient Sample(NIS), a component of the Healthcare Utilization Project (HCUP). Variables were identified using ICD-9-CM codes. We selected inpatient stays for patients aged 11-35 years admitted for sickle cell crisis. Opioid abuse was the primary outcome of interest. Secondary outcomes were inpatient mortality, total charge, length of stay and select clinical outcomes. We analyzed our data for trends and outcomes. We performed trend analysis of prevalence rates between 2007-2014 by age categories. Propensity-Matched Score regression models were deployed to assess for associations between opioid abuse and outcomes while adjusting for relevant covariates. Sub-group analysis of opioid abuse by age was assessed for outcomes of interest. Trend analysis was performed on Joinpoint Software v4.6.0, (National Cancer Institute, NIH, Bethesda, MD). Outcome analysis was performed on SAS v9.4 (SAS Institute, Cary, NC). Statistical significance was set at 95% and p-value of 0.05, two-tailed. RESULTS/ANTICIPATED RESULTS: Of 86, 827 inpatients admitted for sickle cell crisis, 2, 363 (2.73%) had a diagnosis of opioid abuse while 84, 464 (97.27%)did not abuse opioids. 27, 004 (31.01%) of admitted patients were 11-21 years while 59, 823 (68.99%) were 21-35 years. We found statistically significant APCs (Annual Percentage Change) showing increasing trends in both age categories for years under review, (18.47% [95% CI 15.39-21.63]; p-value <0.001 in young adults vs. 10.31% [95% CI 3.58-17.49]; p-value 0.009 in adolescents). The difference in APCs between both age categories were also significant (−8.16% [95% CI [−14.26-2.05]; p-value 0.009). There were no parallelism or coincidence in the trend lines. Opioid abuse was found to be associated with significantly longer length of stay (7.74 vs 6.05 days), higher total charge ($40, 797 vs $32, 164), (aOR 1.44; 95% CI [1.19-1.75]) seizures, sepsis (aOR 1.62; 95% CI [1.35-1.94]) and pulmonary hypertension (aOR 1.36; 95% CI [1.12-1.66]). No significant association was found for inpatient mortality, transfusion, cardiac dysrhythmias, pulmonary embolism and acute kidney injury. Significant interaction existed between opioid abuse and age for total charge (for $41, 869 vs $29, 371 among adolescents & $40, 632 vs $32, 550 among young adults; interaction p-value 0.03). DISCUSSION/SIGNIFICANCE OF IMPACT: Trends show a significant increase in the prevalence of opioid abuse among adolescents and an increasingly higher prevalence when adolescents transition to young adults. Opioid abuse among sickle cell patients is associated with significant poor healthcare resource utilization and clinical outcomes. Public health interventions to prevent worsening opioid abuse prevalence are expected to improve patient outcomes.